Proteomic Analysis of Resistance of Gram-Negative Bacteria to Chlorhexidine and Impacts on Susceptibility to Colistin, Antimicrobial Peptides, and Ceragenins - Hashemi, Marjan M.; Holden, Brett S.; Coburn, Jordan; Taylor, Maddison F.; Weber, Scott; Hilton, Brian; Zaugg, Aaron L.; McEwan, Colten; Carson, Richard; Andersen, Joshua L.; Price, John C.; Deng, Shenglou; et al. (Frontiers in Microbiology, 2019)
Use of chlorhexidine in clinical settings has led to concerns that repeated exposure of bacteria to sub-lethal doses of chlorhexidine might result in chlorhexidine resistance and cross resistance with other cationic antimicrobials including colistin, endogenous antimicrobial peptides (AMPs) and their mimics, ceragenins. We have previously shown that colistin-resistant Gram-negative bacteria remain susceptible to AMPs and ceragenins. Here, we investigated the potential for cross resistance between chlorhexidine, colistin, AMPs and ceragenins by serial exposure of standard strains of Gram-negative bacteria to chlorhexidine to generate resistant populations of organisms. Furthermore, we performed a proteomics study on the chlorhexidine-resistant strains and compared them to the wild type strains to find the pathways by which bacteria develop resistance to chlorhexidine. Serial exposure of Gram-negative bacteria to chlorhexidine resulted in four- to eight-fold increases in minimum inhibitory concentrations (MICs). Notably, chlorhexidine-resistant organisms showed decreased susceptibility to colistin (8- to 32-fold increases in MICs) despite not being exposed to colistin. In contrast, chlorhexidine-resistant organisms had the same MICs as the original strains when tested with representative AMPs (LL-37 and magainin I) and ceragenins (CSA-44 and CSA-131). These results imply that there may be a connection between the emergence of highly colistin-resistant Gram-negative pathogens and the prevalence of chlorhexidine usage. Yet, use of chlorhexidine may not impact innate immune defenses (e.g., AMPs) and their mimics (e.g., ceragenins). Here, we also show that chlorhexidine resistance is associated with upregulation of proteins involved in the assembly of LPS for outer membrane biogenesis and virulence factors in Pseudomonas aeruginosa. Additionally, resistance to chlorhexidine resulted in elevated expression levels of proteins associated with chaperones, efflux pumps, flagella and cell metabolism. This study provides a comprehensive overview of the evolutionary proteomic changes in P. aeruginosa following exposure to chlorhexidine and colistin. These results have important clinical implications considering the continuous application of chlorhexidine in hospitals that could lead to a rapid dissemination of multi-drug resistant strains.